ENTREVISTA: DAVID HARVEY - Arroyo, Mónica (Boletim Paulista de Geografia, 2017)
ENTREVISTA: DAVID HARVEY Mónica Arroyo, Helion Póvoa Neto, Mareia Quintero Rivera e Roberto Morales Urra. 29 de março de 1995, São Paulo. Tradução: Helion Póvoa Neto